Urrets-Zavalia syndrome after deep anterior lamellar keratoplasty - Jovanović Vesna; Nikolić Ljubiša (Vojnosanitetski Pregled)
Introduction. Urrets-Zavalia syndrome is an uncommon complication of the deep anterior lamellar keratoplasty in keratoconus. The manifestations of this syndrome are an irreversible mydriasis, iris atrophy and secondary glaucoma. Case report. Deep anterior lamellar keratoplasty was done for keratoconus with a presumably healed corneal hydrops in a 21-year-old Caucasian man. The graft remained clear, but the surgery was complicated by a fixed, dilated pupil, patches of iris atrophy, ectropium of the iris pigment layer and glaukomflecken in the lens. Conclusion. Although safer than penetrating keratoplasty, the deep anterior lamellar by not trying to secure an unhealed Descemet’s membrane with air. Instead, a new Descemet’s membrane transplanted within a penetrating graft is a safer choice.